Heat transfer on asymmetric thermal viscous dissipative Couette–Poiseuille flow of pseudo-plastic fluids - Tso, Chih Ping. (2013)
Semi-analytical solutions are derived to investigate the effect of viscous dissipation on the temperature distribution and heat transfer characteristics of Couette–Poiseuille flow for pseudo-plastic fluids. The fluid flow is steady, laminar and both hydro-dynamically and thermally fully developed, while the thermal boundary conditions considered are both plates being kept at asymmetric heat fluxes. For Couette–Poiseuille flow for pseudo-plastic fluids, the temperature distribution and the Nusselt number obtained are greatly affected by constant heat flux ratio together with velocity of the moving plate, power-law index, modified Brinkman number and a dimensionless parameter which is the constant of integration in solving the momentum equation.